Histopathological study on some form of bovine pneumonia - THWENI, MAHDI (University of Thi-Qar Journal of Science, 2019)
A total of 1234 cow lungs were examined grossly from apparently healthy adults cows slaughtered at Basra during the period from January 2005 to June 2005. Tissue from pneumonia lungs were collected processed sectioned at5- 6µ and stained for histopathological study conducted on 127 consolidated lungs of adult cows. Pneumonia has been classified according to the type of inflammatory and pulmonary reaction as well as the lesion duration. Pneumonia in the descending order of prevalence were chronic interstitial pneumonia, fibrinous pneumonia, fibrinopurulent pneumonia, acute suppurative pneumonia, lymphoid pneumonia and chronic pneumonia . The prevalence of pneumonia in adult cows on the basis of histopathological examination in this study was 9.5%, the role of the such lesion in cows were discussed.